Association between job strain and working life expectancy: a longitudinal study of older people in Sweden - Chungkham, Holendro Singh; Hoegnäs, Robin; Alexanderson, Kristina; Zaninotto, Paola; Farrants, Kristin; Hyde, Martin; Magnusson Hanson, Linda L.; Head, Jenny; Rugulies, Reiner; Larsen, Ann Dyreborg; Vanajan, Anushiya; Stenholm, Sari; et al. (OXFORD UNIV PRESS, 2025)
Many European countries have increased retirement ages to address the challenge of population ageing. However, job strain which is the combination of high job demands and low job control may be an obstacle to extending the working lives of older workers. Job strain is associated with poor health and early work exit among older workers, but less is known about whether job strain impacts working life expectancy (WLE)-an increasingly employed summary measure capturing the length of working lives. This study aims to fill this gap in the literature. The sample included n = 13 225 individuals aged 50 years or older at baseline providing 53 004 persons-observations from the Swedish Longitudinal Occupational Survey of Health in 2008 through 2020. We used continuous time multi-state Markov models to assess the average number of years people may be expected to work beyond age 50 years by job strain, and stratified by sex, occupational class, and level of education. Job strain was associated with a significantly shorter WLE (by about 6 months to a year) among those who experienced job strain compared to those who did not experience job strain. Our findings suggest that job strain may play a role in shortening the working lives of older people. The findings further suggest that if older workers are to remain in the labor market for longer periods, this may require improvements of psychosocial working conditions.